Kittens in the kitchen - Daniels, Lucy.; McNicholas, Shelagh; Hodder Children's Books (London : Hodder Children's Books, 2004)
When the stray cat she has adopted has kittens in her school caretaker's cottage, he gives Mandy just a week to find homes for the four babies.
"First published in Great Britain in 1994"--T.P. verso.
2.8
3-6
Keywords: Cats -- Fiction; Veterinarians -- Fiction